Frantz’ tumour: a rare pancreatic neoplasm - Ikhwan Sani Mohamad,; Boo, HS; Zamri Zainal,; Affirul C,; Razman Jarmin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Frantz’ tumour of the pancreas is also known as solid pseudopapillary tumour (SPT) of the pancreas. It is a rare pancreatic neoplasm and represents about 3% of all the pancreatic cystic neoplasm. It occurs predominantly in young woman in 2nd to 3rd decade of life. These tumours exhibit indolent behaviour and very often reach considerable size before the first symptoms appear. Despite this presentation these tumours have low malignant potential and complete surgical resection render excellent prognosis. We reported a case of a 16-year-old girl who presented with upper abdominal mass with symptoms of gastric outlet obstruction for 7 months duration. Clinical examination revealed a huge epigastric mass measuring 10 x 12 cm in size. CT scan showed presence of mass arising from the body of the pancreas which was hypervascular, well-encapsulated with mixed cystic and solid components. She then underwent successful distal pancreatectomy and splenectomy and recovered uneventfully.